Exogenously applied Spd and Spm enhance drought tolerance in tea plants by increasing fatty acid desaturation and plasma membrane H+-ATPase activity - Na, Chang; Ziwen, Zhou; Yeyun, Li; Xianchen, Zhang (Plant physiology and biochemistry, 2022)
Polyamines, due to their positive charges, bind to ROS Reactive oxygen species (ROS) thereby stabilizing the plasma membrane (PM). Drought is one of the main limiting factors affecting tea plant yield and quality. However, the effect of Spermidine (Spd) or Spermine (Spm) on membrane stability and fluidity in tea plants under drought stress is poorly understood. In this investigation, an exogenous supply of 1 mM Spd or Spm did not mitigate drought stress-induced damage, however, an exogenous supply of 0.2 mM Spd or Spm application significantly alleviated drought-induced damage in tea plants. To further illustrate the role of 0.2 mM Spd or Spm in maintaining membrane integrity and fluidity, the fatty acid percentage and PM H+-ATPase activity were analyzed. Spd and Spm application significantly increased PM H+-ATPase activity by 43.79% compared with that without the addition of polyamine under drought stress. In addition, exogenous application of Spd and Spm also significantly increased C18:3 by approximately 10%, hence alleviating drought-reduced fatty acid unsaturation. In contrast, Spd and Spm metabolic inhibitors dicyclohexylamine (DCHA) further impaired PM H+-ATPase activity and fatty acid desaturation under the drought + DCHA treatment compared with the drought treatment, respectively. Taken together, 0.2 mM Spd and Spm application significantly enhanced drought tolerance by increasing fatty acid unsaturation and maintaining PM H+-ATPase activity in tea plants. Therefore, foliar application of 0.2 mM Spd or Spm can be a potential foliar-spraying substances for improving tea drought tolerance. •An exogenous supply of 0.2 mM Spd or Spm significantly alleviated drought-induced damage in tea plants.•0.2 mM Spd and Spm application significantly increased drought-reduced plasma membrane H+-ATPase activity and fatty acid unsaturation.